2018
DOI: 10.19044/ejes.v5no2a1
|View full text |Cite
|
Sign up to set email alerts
|

Parental Stress and Parent-Child Relationships in Recently Divorced, Custodial Mothers

Abstract: Divorce often creates significant stress that can have an impact on parent-child relationship satisfaction. The purpose of this study was to examine the predictive relationship between parental stress as measured by the Parenting Stress Index, 4 th Edition, Short Form (PSI-4-SF) and the parentchild relationship satisfaction as measured by the Parent-Child Relationship Inventory (PCRI) following a separation or divorce. A sample of 17 recently separated or divorced, custodial mothers who had at least one child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This finding is in line with findings of several studies that found that the lockdown elevated parental stress and was associated with children’s elevated behavioral and emotional problems, especially hyperactivity and conduct problems (Christner et al, 2021; Spinelli et al, 2020). There are indications that parents who are confronted with high levels of stress and parents with psychological mental problems tend to perceive their children as more difficult and as having more problematic behaviors than do parents without these characteristics (Murphy et al, 2018; Watkins et al, 2013). Parents’ mental health issues and especially their depressive symptoms have been linked with a greater number of negative parenting behaviors including emotional withdrawal from the child, an increase in hostile reactions toward the child, hindered communication with the child, and decreased sensitivity to the child’s needs (Lovejoy et al, 2000; Wilson & Durbin, 2010), all of which may contribute to negative child behaviors (Cummings et al, 2010; Salloum et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with findings of several studies that found that the lockdown elevated parental stress and was associated with children’s elevated behavioral and emotional problems, especially hyperactivity and conduct problems (Christner et al, 2021; Spinelli et al, 2020). There are indications that parents who are confronted with high levels of stress and parents with psychological mental problems tend to perceive their children as more difficult and as having more problematic behaviors than do parents without these characteristics (Murphy et al, 2018; Watkins et al, 2013). Parents’ mental health issues and especially their depressive symptoms have been linked with a greater number of negative parenting behaviors including emotional withdrawal from the child, an increase in hostile reactions toward the child, hindered communication with the child, and decreased sensitivity to the child’s needs (Lovejoy et al, 2000; Wilson & Durbin, 2010), all of which may contribute to negative child behaviors (Cummings et al, 2010; Salloum et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to this perspective, a reciprocal connection exists between the different parts that comprise the family system. Parental stress and mental health problems have been found to influence the parent–child relationship ( Murphy et al, 2018 ; Sanner & Neece, 2018 ), as well as the child’s well-being and problematic behaviors ( Laufer & Shechory Bitton, 2020 ; Najman et al, 2010 ; Puff & Renk, 2014 ; Shechory-Bitton, 2013 ).…”
Section: Introductionmentioning
confidence: 99%